Analysis Of the Effect of Liquidity and Profitability on Tax Aggressiveness in Plantation Subsector Companies Listed on The Indonesia Stock Exchange - Denti Sukma Sastranegara; Hendry Saladin; Ninin Non Ayu Salmah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This research addresses the critical issue of how liquidity and profitability influence tax aggressiveness within companies. The primary objective is to test the hypothesis that both liquidity and profitability significantly affect tax strategies in plantation subsector companies listed on the Indonesia Stock Exchange. Utilizing purposive sampling, the study selected 12 companies that consistently published financial reports from 2018 to 2022. For data analysis, the study employed various techniques, including classical assumption tests, multiple regression analysis, coefficient of determination analysis, correlation coefficient analysis, and hypothesis testing. The findings reveal that liquidity, with a significance value of 0.010, and profitability, with a significance value of 0.000, each partially influence tax aggressiveness. The F-test results further confirm that tax aggressiveness is significantly affected by liquidity and profitability together, as indicated by a p-value of 0.000. These outcomes highlight the importance of both liquidity and profitability as determinants of tax aggressiveness in the plantation sector. The implications of this research suggest that companies can leverage their liquidity and profitability positions to optimize their tax strategies effectively. This study contributes valuable insights for policymakers and business leaders looking to understand the financial factors that drive tax behavior in corporate settings.